A Case Report of Malignant Melanoma of the Sphenoid Sinus - Kiyoaki Tsukahara; Kazuhiro Nakamura; Ray Motohashi; Minoru Endo; Hiroki Sato (Case Reports in Otolaryngology)
Malignant melanoma of the sphenoid sinus is a very rare disease, and only 6 cases have previously been reported. The present case involved a 74-year-old woman who was examined for visual disturbance of the left eye. Computed tomography revealed a soft tissue shadow, but only mucosal hypertrophy was found on opening the sphenoid sinus under general anesthesia. One month postoperatively, visual disturbance of the right eye and paresis of cranial nerve III appeared. Malignant melanoma was diagnosed from biopsy. Multiple bone metastases were identified, but the patient declined active treatment. As a result, palliative care was provided and she died 3 months later. When there is no improvement in postoperative visual acuity as in this case, in consideration of the possibility of neoplastic lesions, rigorous followup including monitoring for neurological symptoms is warranted.